2004
DOI: 10.4049/jimmunol.173.2.797
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism by Which Orally Administered β-1,3-Glucans Enhance the Tumoricidal Activity of Antitumor Monoclonal Antibodies in Murine Tumor Models

Abstract: Antitumor mAb bind to tumors and activate complement, coating tumors with iC3b. Intravenously administered yeast β-1,3;1,6-glucan functions as an adjuvant for antitumor mAb by priming the inactivated C3b (iC3b) receptors (CR3; CD11b/CD18) of circulating granulocytes, enabling CR3 to trigger cytotoxicity of iC3b-coated tumors. Recent data indicated that barley β-1,3;1,4-glucan given orally similarly potentiated the activity of antitumor mAb, leading to enhanced tumor regression and survival. This investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
399
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 430 publications
(420 citation statements)
references
References 38 publications
3
399
0
7
Order By: Relevance
“…The antitumor activity of β -glucans is known and has been reported in several studies with fungal (1 3),(1 6)-β -glucan, such as shizophylan, lentinam (Ooi and Liu 2000;Zhang et al 2005), (1 3),(1 6)-β -glucan from yeast (Kiho et al 1998). It can be explained that after implantation of tumor cells naturally elicited antitumor antibodies most probably occur, and they function similarly to exogenous antitumor mAbs by coating tumor cells with iC3b fragments (Hong et al 2004). Moreover, β -glucan converts the nonprotective Th2-type response, which has been reported as dominant in the course of cancer, to a protective Th1-type response that favors cytotoxic T lymphocytes activity (Baran et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The antitumor activity of β -glucans is known and has been reported in several studies with fungal (1 3),(1 6)-β -glucan, such as shizophylan, lentinam (Ooi and Liu 2000;Zhang et al 2005), (1 3),(1 6)-β -glucan from yeast (Kiho et al 1998). It can be explained that after implantation of tumor cells naturally elicited antitumor antibodies most probably occur, and they function similarly to exogenous antitumor mAbs by coating tumor cells with iC3b fragments (Hong et al 2004). Moreover, β -glucan converts the nonprotective Th2-type response, which has been reported as dominant in the course of cancer, to a protective Th1-type response that favors cytotoxic T lymphocytes activity (Baran et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of β -glucan to enhance the activity of antitumor monoclonal antibodies (mAbs) also requires that they activate complement and deposit iC3b on tumor cells for recognition by CR3 on granulocytes and NK cells (Cheung and Modak 2002;Hong et al 2003). It has been demonstrated that β -glucan from both barley (Cheung and Modak 2002;Modak et al 2005) and yeast (Yan et al 1999;Hong et al 2003Hong et al , 2004Li et al 2006Li et al , 2007 has synergistic effects when used with anticancer mAbs in various tumor models. The mechanism of action has been explained in several studies (Hong et al 2003(Hong et al , 2004Li et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations